2012
DOI: 10.1101/gr.133926.111
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hepatitis B virus integration into the genomes of hepatocellular carcinoma patients

Abstract: Hepatitis B virus (HBV) infection is a leading risk factor for hepatocellular carcinoma (HCC). HBV integration into the host genome has been reported, but its scale, impact and contribution to HCC development is not clear. Here, we sequenced the tumor and nontumor genomes (>803 coverage) and transcriptomes of four HCC patients and identified 255 HBV integration sites. Increased sequencing to 2403 coverage revealed a proportionally higher number of integration sites. Clonal expansion of HBV-integrated hepatocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
283
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(317 citation statements)
references
References 35 publications
28
283
2
4
Order By: Relevance
“…Intriguing recent data showed that hepatitis B virus (HBV) integrants in hepatocellular carcinoma similarly can be associated with regional CNVs, viral-host fusion transcripts and alterations in host genome expression (Jiang et al 2012;Sung et al 2012;Toh et al 2013), analogous to our findings on HPV integrants. However, although CNVs were identified near HBV integrants in ;25% of cases, they and other structural variants were not fully resolved.…”
Section: Discussionsupporting
confidence: 63%
“…Intriguing recent data showed that hepatitis B virus (HBV) integrants in hepatocellular carcinoma similarly can be associated with regional CNVs, viral-host fusion transcripts and alterations in host genome expression (Jiang et al 2012;Sung et al 2012;Toh et al 2013), analogous to our findings on HPV integrants. However, although CNVs were identified near HBV integrants in ;25% of cases, they and other structural variants were not fully resolved.…”
Section: Discussionsupporting
confidence: 63%
“…Various types of mutation spectrum have been found in various tumor with different rates of transitions and transversions (22). In the present study, C:G>T:A transition (50%) that somatic mutation patterns are significantly distinct from the expected spectrum (24,(26)(27)(28). In HCC, the C:G>T:A transition, T:A>C:G transition and C:G>A:T transversion are common mutations; however, in the present study, the C:G>G:C transversion was observed at a high frequency.…”
Section: Tp53 Ctnnb1 Smarcb1 ----------------------------------------mentioning
confidence: 63%
“…Recent studies using next-generation sequencing technologies have highlighted the fact that, following the integration of HBV into the cellular genome, the 39-end of the HBx gene is often deleted and this event is observed more frequently in tumour tissues (Jiang et al, 2012;Sung et al, 2012;Toh et al, 2013). Furthermore, truncated HBx human chimeric transcripts may be seen and expressed as chimeric proteins (Sirma et al, 1999;Toh et al, 2013;Tu et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…These include hot-spot mutations in HBx at aa 130 and 131, which have been associated with the development of HCC (Iavarone et al, 2003;Kuang et al, 2004;Lee et al, 2011). Furthermore, the random integration of HBV DNA into the host genome frequently leads to 39-end-deleted sequences of the HBx gene and the observation of chimeric transcripts which often carry deletions at the 39-end of HBx gene, resulting in C-terminal-truncated HBx protein (Iavarone et al, 2003;Jiang et al, 2012;Ma et al, 2008;Sirma et al, 1999;Sung et al, 2012;Sze et al, 2013;Toh et al, 2013;Tu et al, 2001). Interestingly, a recent study with human HCC samples reports an association between the presence of C-terminal truncation of HBx and venous invasion (Sze et al, 2013).…”
Section: Introductionmentioning
confidence: 99%